2003
DOI: 10.1039/b307443a
|View full text |Cite
|
Sign up to set email alerts
|

Benzophenones in the higher triplet excited states

Abstract: Transient phenomena of benzophenone (BP) in the higher triplet excited state (Tn) have been investigated by the two-colour two-laser excitation method. Triplet energy transfer from BP(Tn) to quenchers (Q) occurred within the duration of a laser pulse (5 ns) to give Q(T1) with higher triplet energy than that of BP(T1). The quantum yield of the triplet energy-transfer quenching of BP(Tn) by CCl4 was found to be 0.0023 +/- 0.0002 from the bleaching of the transient absorption of BP(T1) and the absorbed photon num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
40
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…[11] Recently, we reported the TET from BP(T n ) to various quenchers (Q) to give Q(T 1 ), and the sequential TET from Q(T 1 ) to BP. [13,16] It was found that in the case of p-dichlorobenzene (DCB) as Q, the sequential TET from DCB(T 1 ) to BP occurred with a yield of 100 %; however, the yield for Bz as Q was not 100 %, because of the competitive reactions from Bz(T 1 ). [11,13,16] No sequential TET process was observed for carbon tetrachloride (CCl 4 ) as Q, because of the rapid C À Cl bond cleavage of CCl 4 (T 1 ) to give CCl 3 C and ClC.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…[11] Recently, we reported the TET from BP(T n ) to various quenchers (Q) to give Q(T 1 ), and the sequential TET from Q(T 1 ) to BP. [13,16] It was found that in the case of p-dichlorobenzene (DCB) as Q, the sequential TET from DCB(T 1 ) to BP occurred with a yield of 100 %; however, the yield for Bz as Q was not 100 %, because of the competitive reactions from Bz(T 1 ). [11,13,16] No sequential TET process was observed for carbon tetrachloride (CCl 4 ) as Q, because of the rapid C À Cl bond cleavage of CCl 4 (T 1 ) to give CCl 3 C and ClC.…”
Section: Introductionmentioning
confidence: 97%
“…[13,16] It was found that in the case of p-dichlorobenzene (DCB) as Q, the sequential TET from DCB(T 1 ) to BP occurred with a yield of 100 %; however, the yield for Bz as Q was not 100 %, because of the competitive reactions from Bz(T 1 ). [11,13,16] No sequential TET process was observed for carbon tetrachloride (CCl 4 ) as Q, because of the rapid C À Cl bond cleavage of CCl 4 (T 1 ) to give CCl 3 C and ClC. The lifetimes of BP(T n ) (t Tn ) and several BP derivatives in the T n states have been estimated from the dependence of the quenching efficiency on the concentration of Q ([Q]).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations